Local Justice in America - Elster, Jon, 1940- (Book collections on Project MUSE., 1995)
In framing chapters, editor Jon Elster draws upon these studies to speculate on the unique nature of the American value system. Arguing that race matters deeply in all considerations of local justice, he discusses how our society's assessment of neediness balances on the often uneasy compromises between the desire to reward deserving individuals and the call to strengthen opportunities for disadvantaged groups. Well informed and stimulating, Local Justice in America speaks directly to policy debates in the fields of health, education, work, and immigration, and makes an important contribution to our understanding of the fundamental social issues that affect our daily welfare.